2017
DOI: 10.1016/j.arbr.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Mechanical Ventilation Versus Continuous Positive Airway Pressure Relating to Cardiogenic Pulmonary Edema in an Intensive Care Unit

Abstract: Either NIV or CPAP are recommended in patients with CPE in the ICU. Outcomes in the hypercapnic group with no chronic lung disease were similar using NIV or CPAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The number of studies using the treatment in ACPO was also lower than might be at first expected because many of the studies claiming to be treating a pulmonary edema population and included in prior systematic reviews,[ 20 21 ] in fact included high numbers of patients with coexistent COPD. [ 22 23 24 25 26 27 28 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies using the treatment in ACPO was also lower than might be at first expected because many of the studies claiming to be treating a pulmonary edema population and included in prior systematic reviews,[ 20 21 ] in fact included high numbers of patients with coexistent COPD. [ 22 23 24 25 26 27 28 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
“… 43 Bello and colleagues review of the literature showed that the uses of NIV can decrease the systemic venous return and left ventricular afterload, which would reduce LV filling pressure and limiting pulmonary edema, and that CPAP showed improvement in vital signs of patients and decreased need for endotracheal intubation and hospital mortality than conventional oxygen therapy. 2 , 44 The BTS guidelines recommend CPAP as it has been shown effective in patient with cardiogenic pulmonary edema and that NIV should be reserved for those for whom CPAP is not successful. 3 The ERS/ATS guidelines recommend either bilevel NIV or CPAP for patients with acute respiratory failure due to cardiogenic pulmonary edema.…”
Section: Common Clinical Scenariosmentioning
confidence: 99%